Enhancing the power conversion efficiency of dye-sensitized solar cells via molecular plasmon-like excitations. Issue 16 (25th January 2017) - Li, Jian-Hao; Gryn'ova, Ganna; Prlj, Antonio; Corminboeuf, Clémence
Abstract : We introduce a tactic for employing molecular plasmon-like excitations to enhance solar-to-electric power conversion efficiency of dye-sensitized solar cells. Abstract : We introduce a tactic for employing molecular plasmon-like excitations to enhance solar-to-electric power conversion efficiency of dye-sensitized solar cells. We offer general design principles of dimeric dyes, in which a strong plasmonic interaction between two π-conjugated moieties is promoted. The π-stacked conformations of these dimeric dyes result in a desirable broadened absorption and a longer absorption onset wavelength.